Pole piece, preparation method thereof and battery
By setting the surface density of the positive electrode active material layer to 1.8 to 2.2 times that of the negative electrode active material layer and rolling under the same rolling pressure, the problems of cumbersome and high cost of preparation of bipolar electrodes are solved, and the effects of simplifying the process, reducing costs and improving the feasibility of mass production are achieved.
Patent Information
- Application Number
- CN202411756471.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-04-15
AI Technical Summary
The preparation method of bipolar electrodes is cumbersome and has high cost, which leads to low feasibility of mass production.
By setting the surface density of the positive electrode active material layer on the current collector to 1.8 to 2.2 times the surface density of the negative electrode active material layer, and rolling under the same roller pressure, the process is simplified and the cost is reduced.
The design compaction density of the positive and negative electrode active material layers is achieved without multiple rolling pressures, which simplifies the process, reduces costs, and improves the feasibility of mass production.
Smart Images

Figure CN119833544A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the field of battery technology, and in particular relates to a pole piece, a preparation method thereof, and a battery. Background Art
[0002] Bipolar batteries are composed of bipolar electrodes and diaphragms stacked one layer at a time. The more layers are stacked, the greater the voltage of the battery. Each battery cell in the battery is connected in series, and there are no complex electrical connectors or other structural parts between the battery cells. Therefore, the impedance and voltage consistency between the battery cells are good, making the bipolar battery have a higher energy density. However, due to the different formulations of positive electrode materials, negative electrode materials, and positive and negative electrode slurries, the positive and negative electrode coatings generally require different rolling pressures. In related technologies, the positive and negative electrode coatings of the bipolar electrode are usually rolled separately, and then the rolled coatings are bonded to the current collector by certain means. However, the preparation process of this method is cumbersome and the cost is high, making mass production feasibility not high. Summary of the invention
[0003] The purpose of the present application is to provide a pole piece and a method for preparing the same, and a battery, in order to solve the technical problem that the preparation method of bipolar electrodes is complicated and costly.
[0004] In order to achieve the above application purpose, the technical solution adopted in this application is as follows:
[0005] In a first aspect, the present application provides a method for preparing a pole piece, comprising the following steps:
[0006] preparing positive electrode slurry and negative electrode slurry respectively;
[0007] Providing a current collector, applying a positive electrode slurry to one surface of the current collector along the thickness direction, and after drying, obtaining a positive electrode active material layer; applying a negative electrode slurry to the other surface of the current collector away from the positive electrode active material layer, and after drying, obtaining a negative electrode active material layer;
[0008] The positive electrode active material layer and the negative electrode active material layer of the dried electrode sheet are rolled at the same pressure to obtain a bipolar electrode sheet; wherein the surface density of the positive electrode active material layer on the current collector is 1.8 to 2.2 times the surface density of the negative electrode active material layer.
[0009] In some embodiments, the surface density of the positive electrode active material layer is 138-145 mg / 1540.25 mm 2 The surface density of the negative electrode active material layer is 64-76 mg / 1540.25 mm 2 .
[0010] In some embodiments, the positive electrode slurry includes a positive electrode active material, a first conductive agent and a first binder, and the mass ratio of the positive electrode active material, the first conductive agent and the first binder is: (93-95): (4-6): (0.9-1.1); and / or, the negative electrode slurry includes a negative electrode active material, a second conductive agent, a second binder and a thickener, and the mass ratio of the negative electrode active material, the second conductive agent, the second binder and the thickener is: (95-96.5): (0.5-2): (1.8-2.2): (0.8-1.2).
[0011] In some embodiments, in the width direction of the electrode sheet, the linear force density of the rolling pressure acting on the positive electrode active material layer and the negative electrode active material layer is 2.3-2.5 N / m.
[0012] In some embodiments, the solid content of the positive electrode slurry is 65% to 70%, and / or,
[0013] The solid content of the negative electrode slurry is 50% to 55%.
[0014] In a second aspect, the present application provides a pole piece, comprising:
[0015] current collector;
[0016] The positive electrode active material layer is arranged on one surface of the current collector along the thickness direction;
[0017] The negative electrode active material layer is arranged on the other surface of the current collector away from the positive electrode active material layer;
[0018] The surface density of the positive electrode active material layer on the current collector is 1.8 to 2.2 times that of the negative electrode active material layer.
[0019] In some embodiments, the surface density of the positive electrode active material layer is 138-145 mg / 1540.25 mm 2 The surface density of the negative electrode active material layer is 64-76 mg / 1540.25 mm 2 .
[0020] In some embodiments, the compaction density of the positive electrode active material layer on the current collector is 2.2-2.5 times the compaction density of the negative electrode active material layer.
[0021] In some embodiments, the compaction density of the positive electrode active material layer is 3.2 to 3.6 g / cm 3 The compaction density of the negative electrode active material layer is 1.39 to 1.45 g / cm 3 .
[0022] In some embodiments, the positive electrode active material layer includes a positive electrode active material, a first conductive agent and a first binder, and the mass ratio of the positive electrode active material, the first conductive agent and the first binder is: (93-95): (4-6): (0.9-1.1); and / or, the negative electrode active material layer includes a negative electrode active material, a second conductive agent, a second binder and a thickener, and the mass ratio of the negative electrode active material, the second conductive agent, the second binder and the thickener is: (95-96.5): (0.5-2): (1.8-2.2): (0.8-1.2).
[0023] In some embodiments, the positive electrode active material includes a ternary material, the first conductive agent includes at least one of conductive carbon black, acetylene black or carbon nanotubes, and the first binder includes at least one of polyvinylidene fluoride, polytetrafluoroethylene or polyacrylic acid; and / or,
[0024] The negative electrode active material includes at least one of graphite, silicon-doped graphite or silicon carbon, the second conductive agent includes at least one of conductive carbon black, acetylene black or carbon nanotubes, the second binder includes at least one of styrene-butadiene rubber, sodium alginate or polyvinyl alcohol, and the thickener includes carboxymethyl cellulose or its derivatives.
[0025] In some embodiments, the current collector includes one, or the current collector includes at least two, and the at least two current collectors are conductively connected.
[0026] In a third aspect, the present application further provides a battery, comprising a pole piece prepared by the preparation method described in any one of the first aspect or a pole piece described in any one of the second aspect;
[0027] The solid electrolyte layer is arranged between the positive electrode and the negative electrode of two adjacent pole pieces.
[0028] Based on the above technical solution, the electrode sheet and its preparation method and battery provided by the present application have at least the following beneficial technical effects:
[0029] The first aspect of the present application provides a method for preparing a pole piece, by setting the surface density of the positive electrode active material layer on the current collector to be 1.8 to 2.2 times the surface density of the negative electrode active material layer. Then, the positive electrode active material layer and the negative electrode active material layer of the pole piece can be rolled once at the same pressure to achieve the designed compaction density of the positive electrode active material layer and the negative electrode active material layer, without the need for multiple rolling, thus simplifying the process, reducing costs, and reducing resource waste.
[0030] The pole piece provided in the second aspect of the present application includes a current collector, a positive electrode active material layer and a negative electrode active material layer, wherein the positive electrode active material layer is arranged on one surface of the current collector along the thickness direction; the negative electrode active material layer is arranged on the other surface of the current collector away from the positive electrode active material layer; wherein the surface density of the positive electrode active material layer on the current collector is 1.8 to 2.2 times the surface density of the negative electrode active material layer. By setting the surface density of the positive electrode active material layer to 1.8 to 2.2 times the surface density of the negative electrode active material layer, the positive electrode active material layer and the negative electrode active material layer on the current collector can be rolled under the same rolling pressure to simultaneously achieve the compaction density values designed for the positive electrode active material layer and the negative electrode active material layer. No multiple rolling is required, which simplifies the process, reduces costs, reduces resource waste, and improves the feasibility of mass production. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0032] Figure 1 is a schematic diagram of the structure of a pole piece provided by one or more embodiments of the present application;
[0033] Figure 2 is a schematic diagram of the structure of a pole piece provided by one or more embodiments of the present application;
[0034] Figure 3 This is a state diagram of lithium deposition on the electrode of a battery prepared by the preparation method provided in Comparative Example 1 of the present application after multiple cycles.
[0035] Among them, the reference numerals in the figure are:
[0036] 1-first current collector; 2-second current collector; 3-positive electrode active material layer; 4-negative electrode active material layer; 5-third current collector. DETAILED DESCRIPTION
[0037] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0038] In this application, the term "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural. The character " / " generally indicates that the associated objects are in an "or" relationship.
[0039] In the present application, "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c", can all represent: a, b, c, ab (i.e. a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.
[0040] It should be understood that in the various embodiments of the present application, the size of the serial numbers of the above-mentioned processes does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.
[0041] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "said" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0042] The weight of the relevant components mentioned in the embodiment description of the present application can not only refer to the specific content of each component, but also represent the proportional relationship between the weights of the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the embodiment description of the present application, it is within the scope disclosed in the embodiment description of the present application. Specifically, the mass described in the embodiment description of the present application can be a mass unit known in the chemical industry such as μg, mg, g, kg, etc.
[0043] The terms "first" and "second" are used only for descriptive purposes to distinguish objects such as substances from each other, and should not be understood as indicating or implying relative importance or implicitly indicating the number of indicated technical features. For example, without departing from the scope of the embodiments of the present application, the first XX may also be referred to as the second XX, and similarly, the second XX may also be referred to as the first XX. Thus, features defined as "first" and "second" may explicitly or implicitly include one or more of the features.
[0044] In the related art, for electrodes, the positive electrode slurry is coated on both sides of the positive electrode collector, and the negative electrode slurry is coated on both sides of the negative electrode collector, and then the positive electrode collector and the negative electrode collector are subjected to a baking process respectively to obtain dried positive electrode sheets and negative electrode sheets, and then the positive and negative electrode sheets are rolled respectively to achieve the designed compaction density of the positive and negative electrodes. For bipolar electrodes, one side of the current collector is coated with positive electrode slurry, and the other side is coated with negative electrode slurry. Usually, the designed compaction density of the positive electrode active material layer and the negative electrode active material layer is different. Therefore, the rolling pressure required for the positive electrode active material layer and the negative electrode active material layer is very different. If the rolling is carried out at a low compaction density, the other side will not be able to reach the compaction density, resulting in an increase in the thickness of the electrode sheet and an increase in impedance, which is not conducive to the rapid charging and discharging of the battery; if the rolling is carried out at a high compaction density, the other side will be over-pressurized. For example, if the negative electrode active material layer is over-pressurized, it will cause insufficient lithium insertion in the negative electrode, and even cause safety problems due to lithium precipitation in the negative electrode; and if the positive electrode active material layer is over-pressurized, the porosity of the positive electrode active material will be reduced, which will hinder the movement of the electrolyte and lithium ions and increase the internal resistance. In the related art, the positive and negative active material layers of the bipolar electrode are usually rolled separately, and then the rolled coating is bonded to the current collector by certain means, but the preparation process of this method is cumbersome, the cost is high, and the feasibility of mass production is not high.
[0045] Based on the above considerations, in order to solve the technical problems of complicated and high cost in the preparation method of bipolar electrodes in the prior art.
[0046] The embodiment of the present application provides a method for preparing an electrode sheet, comprising the following steps: preparing a positive electrode slurry and a negative electrode slurry respectively; providing a current collector, applying the positive electrode slurry to a surface of the current collector along the thickness direction, and obtaining a positive electrode active material layer after drying; applying the negative electrode slurry to the other surface of the current collector away from the positive electrode active material layer, and obtaining a negative electrode active material layer after drying; rolling the positive electrode active material layer and the negative electrode active material layer of the dried electrode sheet at the same pressure to obtain a bipolar electrode sheet; wherein the surface density of the positive electrode active material layer on the current collector is 1.8 to 2.2 times that of the surface density of the negative electrode active material layer.
[0047] In the technical solution of the embodiment of the present application, by setting the surface density of the positive active material layer to 1.8 to 2.2 times the surface density of the negative active material layer, the positive active material layer and the negative active material layer on the current collector can be rolled under the same rolling pressure to simultaneously reach the compaction density values designed for the positive active material layer and the negative active material layer. No multiple rolling is required, which simplifies the process, reduces costs, reduces resource waste, and improves the feasibility of mass production. This solves the problem of resource waste caused by multiple rolling, material waste caused by negative electrode overvoltage, or excessive battery thickness and impedance caused by positive electrode undervoltage.
[0048] It is understood that the current collector can be at least one of aluminum foil, copper foil, nickel foil, stainless steel foil, aluminum-nickel composite foil, and aluminum-copper composite foil. Surface density refers to the mass per unit area.
[0049] In one or more embodiments of the present application, the surface density of the positive electrode active material layer is 138-145 mg / 1540.25 mm 2 , for example, it can be 138mg / 1540.25mm 2 、141mg / 1540.25mm 2 or 145mg / 1540.25mm 2 The surface density of the negative electrode active material layer is 64-76 mg / 1540.25 mm 2 , for example, it can be 64mg / 1540.25mm 2 、67mg / 1540.25mm 2 or 76mg / 1540.25mm 2 In some embodiments, the ratio of the area density of the positive electrode active material layer to the area density of the negative electrode active material layer may be 1.82, 1.91, 2.06, 2.10, 2.16, or 2.20.
[0050] In one or more embodiments of the present application, the compaction density of the positive electrode active material layer on the current collector is 2.2-2.5 times the compaction density of the negative electrode active material layer. In some embodiments, the compaction density of the positive electrode active material layer is 3.21-3.6 g / cm 3 , for example: 3.21 g / cm 3 、3.22g / cm 3 , 3.25g / cm 3 、3.41g / cm 3 、3.47g / cm 3 or 3.6g / cm 3 The compaction density of the negative electrode active material layer is 1.39-1.45 g / cm 3 , for example, it can be 1.39 g / cm 3 , 1.41g / cm 3 , 1.44g / cm 3 or 1.45g / cm 3 In some embodiments, the ratio of the compaction density of the positive electrode active material layer to the compaction density of the negative electrode active material layer on the current collector may be 2.24, 2.28, 2.3, 2.35, or 2.5.
[0051] It can be understood that compacted density refers to the mass contained in a unit volume.
[0052] In the technical solution of the embodiment of the present application, through the above arrangement, the positive electrode active material layer and the negative electrode active material layer on the current collector are rolled under the same rolling pressure to simultaneously achieve the designed compaction density values of the positive electrode active material layer and the negative electrode active material layer, thereby reducing costs, reducing resource waste, and improving the feasibility of mass production.
[0053] In one or more embodiments of the present application, the positive electrode active material layer includes a positive electrode active material, a first conductive agent, and a first binder, and the mass ratio of the positive electrode active material, the first conductive agent, and the first binder is: (93-95): (4-6): (0.9-1.1). The negative electrode active material layer includes a negative electrode active material, a second conductive agent, a second binder, and a thickener, and the mass ratio of the negative electrode active material, the second conductive agent, the second binder, and the thickener is: (95-96.5): (0.5-2): (1.8-2.2): (0.8-1.2).
[0054] In one or more embodiments of the present application, the mass ratio of the positive electrode active material, the first conductive agent and the first binder is: (93-95): (4-6): 1. The mass ratio of the negative electrode active material, the second conductive agent, the second binder and the thickener is: (95-96.5): (0.5-2): 2: 1.
[0055] The positive electrode active material includes a ternary material, including but not limited to a nickel cobalt manganese (NCM) ternary material and a nickel cobalt aluminum (NCA) ternary material. The first conductive agent includes at least one of conductive carbon black (Super P), acetylene black or carbon nanotubes, and the first binder includes at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene or polyacrylic acid. The negative electrode active material includes at least one of graphite, silicon-doped graphite or silicon carbon. The second conductive agent includes at least one of conductive carbon black (Super P), acetylene black or carbon nanotubes, the second binder includes at least one of styrene-butadiene rubber, sodium alginate or polyvinyl alcohol, and the thickener includes carboxymethyl cellulose or a derivative thereof.
[0056] In the technical solution of the embodiment of the present application, the above-mentioned setting is adopted to realize the relationship between the surface density of the positive electrode active material layer and the surface density of the negative electrode active material layer, so that the positive electrode active material layer and the negative electrode active material layer can reach the designed value of their respective compaction density under the same rolling pressure. When the mass proportion of the positive electrode active material is greater than the above-mentioned range value, a greater rolling pressure is required to reach the designed compaction density, which will cause the negative electrode active material layer to be over-pressurized, and further lead to the problem of insufficient lithium insertion in the negative electrode active material layer; and when the mass proportion of the negative electrode active material is less than the above-mentioned range value, rolling according to the compaction density of the negative electrode active material layer will not achieve the compaction density designed for the positive electrode active material layer, which will easily lead to the positive electrode active material layer being too thick and the impedance becoming larger, which is not conducive to the rapid charging and discharging of the battery.
[0057] In one or more embodiments of the present application, in the width direction of the electrode sheet, the linear force density of the rolling pressure acting on the positive electrode active material layer and the negative electrode active material layer is 2.3-2.5 N / m.
[0058] The linear force density refers to the pressure of the force position on the pole piece during rolling on a unit length in the width direction of the pole piece. The width direction of the pole piece may refer to the direction perpendicular to the rolling direction of the pole piece.
[0059] In the technical solution of the embodiment of the present application, the linear force density of the rolling pressure acting on the positive active material layer and the negative active material layer is set to 2.3-2.5N / m, so that the positive active material layer and the negative active material layer can be simultaneously acted on by a one-time rolling pressure, and the designed compaction density of the positive active material layer and the negative active material layer can be achieved, thereby simplifying the rolling process, reducing costs, reducing resource waste, and improving the feasibility of mass production.
[0060] In one or more embodiments of the present application, the solid content of the positive electrode slurry is 65% to 70%.
[0061] In the technical solution of the embodiment of the present application, the solid content of the positive electrode slurry is set within the above range so as to improve the electrochemical performance of the positive electrode active material and increase the capacity and cycle life of the battery.
[0062] In one or more embodiments of the present application, the solid content of the negative electrode slurry is 50% to 55%.
[0063] In the technical solution of the embodiment of the present application, the solid content of the negative electrode slurry is set within the above range to increase the density and energy density of the negative electrode material, while making the negative electrode active material have good electrical conductivity and mechanical strength, thereby making the battery have excellent performance.
[0064] In one or more embodiments of the present application, a method for preparing a bipolar electrode sheet includes the following steps:
[0065] (1) adding a positive electrode active material, a first conductive agent, and a first binder into a stirring tank, and adding a negative electrode active material, a second conductive agent, a second binder, and a thickener into another stirring tank;
[0066] (2) adding NMP and deionized water to the positive electrode stirring tank and the negative electrode stirring tank respectively, stirring evenly to obtain positive electrode slurry and negative electrode slurry respectively, and storing them in two transfer tanks respectively, wherein the solid content of the obtained positive electrode slurry is 65% to 70%, and the solid content of the obtained negative electrode slurry is 50% to 55%;
[0067] (3) applying the negative electrode slurry to one side of the current collector by extrusion coating, drying the negative electrode active material layer in an oven, applying the positive electrode slurry to the other side of the current collector, and then drying the positive electrode active material layer in an oven;
[0068] (4) The dried electrode is rolled on a roller press at a certain pressure to obtain a bipolar electrode.
[0069] On the other hand, the present application provides a pole piece, including a current collector, a positive electrode active material layer and a negative electrode active material layer, wherein the positive electrode active material layer is arranged on one surface of the current collector along the thickness direction; the negative electrode active material layer is arranged on the other surface of the current collector away from the positive electrode active material layer; wherein the surface density of the positive electrode active material layer on the current collector is 1.8 to 2.2 times the surface density of the negative electrode active material layer.
[0070] In the technical solution of the embodiment of the present application, by setting the surface density of the positive active material layer to 1.8 to 2.2 times the surface density of the negative active material layer, the positive active material layer and the negative active material layer on the current collector can be rolled under the same rolling pressure to simultaneously reach the compaction density values designed for the positive active material layer and the negative active material layer. No multiple rolling is required, which simplifies the process, reduces costs, reduces resource waste, and improves the feasibility of mass production. This solves the problem of resource waste caused by multiple rolling, material waste caused by negative electrode overvoltage, or excessive battery thickness and impedance caused by positive electrode undervoltage.
[0071] Optionally, the surface density of the positive electrode active material layer is 138 to 145 mg / 1540.25 mm 2 , for example, it can be 138mg / 1540.25mm 2 、141mg / 1540.25mm 2 or 145mg / 1540.25mm 2 The surface density of the negative electrode active material layer is 64-76 mg / 1540.25 mm 2, for example, it can be 64mg / 1540.25mm 2 、67mg / 1540.25mm 2 or 76mg / 1540.25mm 2 In some embodiments, the ratio of the area density of the positive electrode active material layer to the area density of the negative electrode active material layer may be 1.82, 1.91, 2.06, 2.10, 2.16, or 2.20.
[0072] In one or more embodiments of the present application, the compaction density of the positive electrode active material layer on the current collector is 2.2-2.5 times the compaction density of the negative electrode active material layer. In some embodiments, the compaction density of the positive electrode active material layer is 3.21-3.6 g / cm 3 , for example: 3.21 g / cm 3 、3.22g / cm 3 , 3.25g / cm 3 、3.41g / cm 3 、3.47g / cm 3 or 3.6 g / cm 3 The compaction density of the negative electrode active material layer is 1.39-1.45 g / cm 3 , for example, it can be 1.39 g / cm 3 , 1.41g / cm 3 , 1.44g / cm 3 or 1.45g / cm 3 In some embodiments, the ratio of the compaction density of the positive electrode active material layer to the compaction density of the negative electrode active material layer on the current collector may be 2.24, 2.28, 2.3, 2.35, or 2.5.
[0073] In the technical solution of the embodiment of the present application, through the above arrangement, the positive electrode active material layer and the negative electrode active material layer on the current collector are rolled under the same rolling pressure to simultaneously achieve the designed compaction density values of the positive electrode active material layer and the negative electrode active material layer, thereby reducing costs, reducing resource waste, and improving the feasibility of mass production.
[0074] In one or more embodiments of the present application, the positive electrode active material layer includes a positive electrode active material, a first conductive agent, and a first binder, and the mass ratio of the positive electrode active material, the first conductive agent, and the first binder is: (93-95): (4-6): (0.9-1.1). The negative electrode active material layer includes a negative electrode active material, a second conductive agent, a second binder, and a thickener, and the mass ratio of the negative electrode active material, the second conductive agent, the second binder, and the thickener is: (95-96.5): (0.5-2): (1.8-2.2): (0.8-1.2).
[0075] In one or more embodiments of the present application, the mass ratio of the positive electrode active material, the first conductive agent and the first binder is: (93-95): (4-6): 1. The mass ratio of the negative electrode active material, the second conductive agent, the second binder and the thickener is: (95-96.5): (0.5-2): 2: 1.
[0076] The positive electrode active material includes a ternary material, including but not limited to a nickel cobalt manganese (NCM) ternary material and a nickel cobalt aluminum (NCA) ternary material. The first conductive agent includes at least one of conductive carbon black (Super P), acetylene black or carbon nanotubes, and the first binder includes at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene or polyacrylic acid. The negative electrode active material includes at least one of graphite, silicon-doped graphite or silicon carbon. The second conductive agent includes at least one of conductive carbon black (Super P), acetylene black or carbon nanotubes, the second binder includes at least one of styrene-butadiene rubber, sodium alginate or polyvinyl alcohol, and the thickener includes carboxymethyl cellulose or a derivative thereof.
[0077] In the technical solution of the embodiment of the present application, the above-mentioned setting is adopted to realize the relationship between the surface density of the positive electrode active material layer and the surface density of the negative electrode active material layer, so that the positive electrode active material layer and the negative electrode active material layer can reach the designed value of their respective compaction density under the same rolling pressure. When the mass proportion of the positive electrode active material is greater than the above-mentioned range value, a greater rolling pressure is required to reach the designed compaction density, which will cause the negative electrode active material layer to be over-pressurized, and further lead to the problem of insufficient lithium insertion in the negative electrode active material layer; and when the mass proportion of the negative electrode active material is less than the above-mentioned range value, rolling according to the compaction density of the negative electrode active material layer will not achieve the compaction density designed for the positive electrode active material layer, which will easily lead to the positive electrode active material layer being too thick and the impedance becoming larger, which is not conducive to the rapid charging and discharging of the battery.
[0078] In one or more embodiments of the present application, the current collector includes one, or the current collector includes at least two, and the at least two current collectors are conductively connected.
[0079] For example: Figure 1 As shown, Figure 1 The longitudinal cross-sectional structure diagram of a bipolar electrode plate of one or more embodiments of the present application is shown, wherein the plate comprises a first current collector 1 and a second current collector 2, wherein the first current collector 1 and the second current collector 2 are bonded by a conductive tape 12. A positive electrode active material layer 3 is coated on the side of the first current collector 1 away from the conductive tape 12, and a negative electrode active material layer 4 is coated on the side of the second current collector 2 away from the conductive tape 12. Or as Figure 2 As shown, Figure 2A schematic diagram of the longitudinal cross-section structure of a bipolar electrode plate of one or more embodiments of the present application is shown, wherein the plate includes a third current collector 5, a positive electrode active material layer 3 is coated on one side of the third current collector 5, and a negative electrode active material layer 4 is coated on the other side of the third current collector 5 away from the positive electrode active material layer 3.
[0080] On the other hand, an embodiment of the present application provides a battery, comprising the pole piece according to any one of the first aspect or the pole piece prepared by the preparation method according to any one of the second aspect; and
[0081] The solid electrolyte layer is arranged between the positive electrode and the negative electrode of two adjacent pole pieces.
[0082] In the technical solution of the embodiment of the present application, through the above-mentioned setting, the bipolar electrodes and the solid electrolyte layer are assembled to form a bipolar solid-state battery, which reduces the production cost of the battery, reduces the waste of resources, and maintains the electrochemical performance and safety performance of the battery.
[0083] The battery provided in the present application can be used as a power source for an electrical device or as an energy storage unit for an electrical device. Electrical devices may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.
[0084] The following describes the invention in conjunction with specific embodiments.
[0085] Example 1
[0086] The preparation method of the bipolar electrode of this embodiment 1 is as follows:
[0087] (1) Add the positive electrode active material, the first conductive agent and the first binder into a stirring tank, wherein the active material lithium nickel cobalt manganese oxide accounts for 93.0% by mass, the first conductive agent Super P accounts for 6.0% by mass, and the first binder PVDF accounts for 1.0% by mass; add the negative electrode active material, the second conductive agent, the second binder and the thickener into another stirring tank; the negative electrode active material graphite accounts for 95.0% by mass, the second conductive agent Super P accounts for 2.0% by mass, the second binder SBR accounts for 2.0% by mass, and the thickener CMC accounts for 1.0% by mass.
[0088] (2) Add NMP and deionized water to the positive electrode stirring tank and the negative electrode stirring tank respectively, stir evenly to obtain positive electrode slurry and negative electrode slurry respectively, and store them in two transfer tanks respectively. The solid content of the obtained positive electrode slurry is 70%, and the solid content of the obtained negative electrode slurry is 55%.
[0089] (3) Preparation Figure 1 The bipolar electrode structure shown in the figure, wherein the first current collector 1 is made of aluminum foil with a thickness of 10 μm, and the second current collector 2 is made of copper foil with a thickness of 6 μm, and the aluminum foil of the first current collector 1 and the copper foil of the second current collector 2 are bonded by a conductive tape 12. The positive electrode slurry is coated on the upper surface of the first current collector 1. After the positive electrode slurry is baked in an oven, the surface density is 138 mg / 1540.25 mm 2 The cathode active material layer 3 is formed. Then, the anode slurry is coated on the lower surface of the second current collector 2. The anode slurry is baked in an oven to form a surface density of 67 mg / 1540.25 mm 2 of the negative electrode coating.
[0090] (4) Finally, the compaction density of the positive electrode active material layer 3 was 3.21 g / cm by rolling at a linear force density of 2.4 N / m. 3 The compaction density of the negative electrode active material layer 4 is 1.41 g / cm 3 of bipolar electrodes.
[0091] Example 2
[0092] The difference between this embodiment 2 and embodiment 1 is that:
[0093] The active material of the positive electrode active material layer 3 is 94.0% by mass of lithium nickel cobalt manganese oxide, the first conductive agent Super P is 5.0% by mass, and the first binder PVDF is 1.0% by mass. The active material of the negative electrode active material layer 4 is 95.75% by mass of graphite, the second conductive agent Super P is 1.25% by mass, the second binder SBR is 2.0% by mass, and the thickener CMC is 1.0% by mass. After drying, the surface density of the positive electrode active material layer 3 is 145mg / 1540.25mm 2 The surface density of the negative electrode active material layer 4 is 76 mg / 1540.25 mm 2 After rolling at a linear force density of 2.4 N / m, the compaction density of the positive electrode active material layer 4 was 3.41 g / cm 3 The compaction density of the negative electrode active material layer 4 is 1.45 g / cm 3 of bipolar electrodes.
[0094] Example 3
[0095] The difference between this embodiment 3 and embodiment 1 is that:
[0096] The active material of the positive electrode active material layer 3 is 95.0% by mass of lithium nickel cobalt manganese oxide, the first conductive agent Super P is 4.0% by mass, and the first binder PVDF is 1.0% by mass. The active material of the negative electrode active material layer 4 is 96.5% by mass of graphite, the second conductive agent Super P is 0.5% by mass, the second binder SBR is 2.0% by mass, and the thickener CMC is 1.0% by mass. After drying, the surface density of the positive electrode active material layer 3 is 141mg / 1540.25mm 2 The surface density of the negative electrode active material layer 4 is 64 mg / 1540.25 mm 2 After rolling at a linear force density of 2.4 N / m, the compaction density of the positive electrode active material layer 3 was 3.60 g / cm 3 The compaction density of the negative electrode active material layer 4 is 1.44 g / cm 3 of bipolar electrodes.
[0097] Example 4
[0098] This Example 4 was prepared as Figure 2 The bipolar electrode structure shown in the figure, the difference between the bipolar electrode of this embodiment 4 and that of embodiment 1 is:
[0099] Pure aluminum foil is used as the third current collector 5 of the bipolar electrode, and the positive electrode slurry is coated on one side of the third current collector 5, and the negative electrode slurry is coated on the other side of the third current collector 5. Among them, the active material of the positive electrode active material layer 3 is 95.0% by mass of lithium nickel cobalt manganese oxide, the first conductive agent Super P is 4.0% by mass, and the first binder PVDF is 1.0% by mass. The active material graphite of the negative electrode active material layer 4 accounts for 95% by mass, the second conductive agent Super P accounts for 2% by mass, the second binder SBR accounts for 2.0% by mass, and the thickener CMC accounts for 1.0% by mass. After drying, the surface density of the positive electrode active material layer 3 is 141mg / 1540.25mm 2 The surface density of the negative electrode active material layer 4 is 67 mg / 1540.25 mm 2 After rolling at a linear force density of 2.4 N / m, the compaction density of the positive electrode active material layer 3 was 3.47 g / cm 3 The compaction density of the negative electrode active material layer 4 is 1.39 g / cm 3 of bipolar electrodes.
[0100] Example 5
[0101] The difference between this embodiment 5 and embodiment 1 is that:
[0102] The active material of the positive electrode active material layer 3 is 93.0% by mass of lithium nickel cobalt manganese oxide, the first conductive agent Super P is 6.0% by mass, and the first binder PVDF is 1.0% by mass. The active material of the negative electrode active material layer 4 is 96.5% by mass of graphite, the second conductive agent Super P is 0.5% by mass, the second binder SBR is 2.0% by mass, and the thickener CMC is 1.0% by mass. After drying, the surface density of the positive electrode active material layer 3 is 138mg / 1540.25mm 2 The surface density of the negative electrode active material layer 4 is 64 mg / 1540.25 mm 2 After rolling at a linear force density of 2.4 N / m, the compaction density of the positive electrode active material layer 4 was 3.25 g / cm 3 The compaction density of the negative electrode active material layer 4 is 1.41 g / cm 3 of bipolar electrodes.
[0103] Example 6
[0104] The difference between this embodiment 6 and embodiment 1 is that:
[0105] The active material of the positive electrode active material layer 3 is 93.0% by mass of lithium nickel cobalt manganese oxide, the first conductive agent Super P is 6.0% by mass, and the first binder PVDF is 1.0% by mass. The active material of the negative electrode active material layer 4 is 95.75% by mass of graphite, the second conductive agent Super P is 1.25% by mass, the second binder SBR is 2.0% by mass, and the thickener CMC is 1.0% by mass. After drying, the surface density of the positive electrode active material layer 3 is 138mg / 1540.25mm 2 The surface density of the negative electrode active material layer 4 is 76 mg / 1540.25 mm 2 After rolling at a linear force density of 2.4 N / m, the compaction density of the positive electrode active material layer 4 was 3.22 g / cm 3 The compaction density of the negative electrode active material layer 4 is 1.44 g / cm 3 of bipolar electrodes.
[0106] Comparative Example 1
[0107] The difference between this comparative example 1 and embodiment 2 is:
[0108] The active material of the positive electrode slurry is lithium nickel cobalt manganese oxide, accounting for 92.0% by weight, the conductive agent Super P accounts for 6.5% by weight, and the first binder PVDF accounts for 1.5% by weight. The surface density of the positive electrode active material layer obtained after drying is 126 / 1540.25mm 2The linear force density of the roller pressing was 2.4 N / m and 2.6 N / m respectively. The compaction density of the positive electrode active material layer 3 obtained after roller pressing was 2.76 g / cm 3 and 3.33 g / cm 3 The compaction density of the negative electrode active material layer 4 is 1.51 g / cm 3 and 1.79 g / cm 3 , the rest is the same as Example 2.
[0109] Comparative Example 2
[0110] The difference between this comparative example 2 and embodiment 2 is:
[0111] The mass proportion of the active material graphite of the negative electrode slurry is 94.0%, the mass proportion of the second conductive agent Super P is 2.0%, the mass proportion of the second binder SBR is 2.0%, and the mass proportion of the thickener CMC is 2.0%. The surface density of the negative electrode active material layer obtained after drying is 61 / 1540.25mm 2 The linear force density of the roller pressing was 2.4 N / m and 2.6 N / m respectively. The compaction density of the positive electrode active material layer 3 obtained after roller pressing was 3.44 g / cm 3 and 3.77 g / cm 3 The compaction density of the negative electrode active material layer 4 is 1.27 g / cm 3 and 1.4 g / cm 3 , the rest is the same as Example 2.
[0112] Comparative Example 3
[0113] The difference between this comparative example 3 and embodiment 2 is that:
[0114] The active material of the positive electrode slurry is lithium nickel cobalt manganese oxide, accounting for 96.0% by weight, the conductive agent Super P accounts for 3% by weight, and the first binder PVDF accounts for 1% by weight. The surface density of the positive electrode active material layer obtained after drying is 130 / 1540.25mm 2 The linear force density of the roller pressing was 2.4 N / m and 2.6 N / m respectively. The compaction density of the positive electrode active material layer 3 obtained after roller pressing was 2.99 g / cm 3 and 3.36 g / cm 3 The compaction density of the negative electrode active material layer 4 is 1.42 g / cm 3 and 1.64 g / cm 3 , the rest is the same as Example 2.
[0115] Comparative Example 4
[0116] The difference between this comparative example 4 and embodiment 2 is that:
[0117] The active material graphite of the negative electrode slurry accounts for 97.5% by mass, the second conductive agent Super P accounts for 1.0% by mass, the second binder SBR accounts for 1.0% by mass, and the thickener CMC accounts for 0.5% by mass. The surface density of the negative electrode active material layer obtained after drying is 60 / 1540.25mm 2 The linear force density of the roller pressing was 2.4 N / m and 2.6 N / m respectively. The compaction density of the positive electrode active material layer 3 obtained after roller pressing was 3.44 g / cm 3 and 3.76 g / cm 3 The compaction density of the negative electrode active material layer 4 is 1.29 g / cm 3 and 1.4 g / cm 3 , the rest is the same as Example 2.
[0118] Table 1 Parameters of Examples 1 to 4 and Comparative Examples 1 to 2
[0119]
[0120]
Performance test
[0121] The bipolar electrodes prepared in the above-mentioned Examples 1 to 6 and Comparative Examples 1 to 4 were stacked layer by layer, separated by solid electrolytes, and then hot-pressed with aluminum-plastic films to obtain bipolar batteries. The bipolar batteries were subjected to AC internal resistance tests and cyclic lithium deposition tests at room temperature.
[0122] The AC internal resistance test process is: use the positive and negative probes of the voltage internal resistance meter to contact the positive and negative electrodes of the battery, and read the internal resistance value displayed by the instrument. The cyclic lithium deposition test process is: 0.5C constant current charging to the upper limit voltage, then charging to 0.05C at the upper limit voltage constant voltage, leaving it for half an hour, then discharging at 0.5C to the lower limit voltage, leaving it for half an hour, repeating the above process 50 times, fully charging the battery, disassembling it, and observing the negative electrode interface. The test results of Examples 1 to 6 and Comparative Examples 1 to 4 are shown in Table 2.
[0123] Table 2 Experimental results of Examples 1 to 6 and Comparative Examples 1 to 4
[0124] AC internal resistance Whether lithium is deposited Example 1 1.43 no Example 2 1.42 no Example 3 1.39 no Example 4 1.41 no Example 5 1.35 no Example 6 1.42 no Comparative Example 1 (A) 1.61 no Comparative Example 1 (B) 1.68 yes Comparative Example 2 (A) 1.56 no Comparative Example 2 (B) 1.57 no Comparative Example 3 (A) 1.59 no Comparative Example 3 (B) 1.66 yes Comparative Example 4 (A) 1.54 no Comparative Example 4 (B) 1.58 no
[0125] Result analysis:
[0126] The internal resistance of the bipolar batteries prepared from Examples 1 to 6 is not large, and there will be no lithium plating problem. In Comparative Example 1, the mass proportion of the positive electrode active material is less than 93%, and the ratio of the surface density of the positive electrode active material layer to the surface density of the negative electrode active material layer is less than 1.8. Among them, the rolling pressure of the bipolar electrode prepared in Comparative Example 1 (A) is based on the compaction density of the negative electrode during rolling, which results in insufficient compaction density of the positive electrode, resulting in an increase in the internal resistance of the battery. The rolling pressure of the bipolar electrode prepared in Comparative Example 1 (B) is based on the compaction density of the positive electrode during rolling, resulting in an overpressure of the compaction density of the negative electrode, resulting in an increase in the internal resistance of the battery, and the occurrence of lithium plating, such as Figure 3 shown.
[0127] In Comparative Example 2, the mass proportion of the negative electrode active material is less than 95%, and the surface density ratio is greater than 2.2. Among them, the rolling pressure of the bipolar electrode prepared in Comparative Example 2 (A) is based on the compaction density of the positive electrode during rolling, which results in insufficient compaction density of the negative electrode, resulting in a large thickness of the battery and a large internal resistance. The rolling pressure of the bipolar electrode prepared in Comparative Example 2 (B) is based on the compaction density of the negative electrode during rolling, resulting in excessive compaction density of the positive electrode, overpressure of the positive electrode, low porosity of the positive electrode active material, and large internal resistance.
[0128] In Comparative Example 3, the mass proportion of the positive electrode active material is greater than 95%, and the ratio of the surface density of the positive electrode active material layer to the surface density of the negative electrode active material layer is less than 1.8. In particular, the rolling pressure of the bipolar electrode prepared in Comparative Example 3 (A) is based on the negative electrode compaction density during rolling, resulting in insufficient positive electrode compaction, resulting in a thicker positive electrode active material layer and an increased internal resistance of the battery. The rolling pressure of the bipolar electrode prepared in Comparative Example 3 (B) is based on the positive electrode compaction density during rolling, resulting in overpressure of the negative electrode, resulting in an increased internal resistance of the battery, and lithium deposition occurs after the battery has been cycled multiple times.
[0129] In Comparative Example 4, the mass proportion of the negative electrode active material is greater than 96.5%, and the ratio of the surface density of the positive electrode active material layer to the surface density of the negative electrode active material layer is greater than 2.2. In particular, the rolling pressure of the bipolar electrode prepared in Comparative Example 4 (A) is based on the positive electrode compaction density during rolling, resulting in insufficient compaction of the negative electrode, making the negative electrode active material layer thicker and the internal resistance of the battery larger. The rolling pressure of the bipolar electrode prepared in Comparative Example 4 (B) is based on the negative electrode compaction density during rolling, which will result in excessive positive electrode compaction density, positive electrode overpressure, low porosity of the positive electrode active material layer, and large internal resistance of the battery.
[0130] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.
Claims
1. A method for preparing a pole piece, characterized in that: The steps include: preparing positive electrode slurry and negative electrode slurry respectively; Providing a current collector, applying the positive electrode slurry to one surface of the current collector along the thickness direction, and after drying, obtaining a positive electrode active material layer; applying the negative electrode slurry to the other surface of the current collector away from the positive electrode active material layer, and after drying, obtaining a negative electrode active material layer; The positive electrode active material layer and the negative electrode active material layer of the dried electrode sheet are rolled at the same pressure to obtain a bipolar electrode sheet; wherein the surface density of the positive electrode active material layer on the current collector is 1.8 to 2.2 times the surface density of the negative electrode active material layer; Optionally, the surface density of the positive electrode active material layer is 138-145 mg / 1540.25 mm 2 The surface density of the negative electrode active material layer is 64-76 mg / 1540.25 mm 2 .
2. The preparation method according to claim 1, characterized in that: The positive electrode slurry comprises a positive electrode active material, a first conductive agent and a first binder, wherein the mass ratio of the positive electrode active material, the first conductive agent and the first binder is: (93-95): (4-6): (0.9-1.1); and / or, The negative electrode slurry includes a negative electrode active material, a second conductive agent, a second binder and a thickener, and the mass ratio of the negative electrode active material, the second conductive agent, the second binder and the thickener is: (95-96.5): (0.5-2): (1.8-2.2): (0.8-1.2).
3. The preparation method according to claim 1, characterized in that: In the width direction of the electrode sheet, the linear force density of the rolling pressure acting on the positive electrode active material layer and the negative electrode active material layer is 2.3-2.5 N / m.
4. The preparation method according to claim 1, characterized in that: The solid content of the positive electrode slurry is 65% to 70%, and / or, The solid content of the negative electrode slurry is 50% to 55%.
5. A pole piece, characterized in that: include: current collector; A positive electrode active material layer is disposed on a surface of the current collector along the thickness direction; A negative electrode active material layer is disposed on the other surface of the current collector away from the positive electrode active material layer; Wherein, the surface density of the positive electrode active material layer on the current collector is 1.8 to 2.2 times the surface density of the negative electrode active material layer; Optionally, the surface density of the positive electrode active material layer is 138-145 mg / 1540.25 mm 2 The surface density of the negative electrode active material layer is 64-76 mg / 1540.25 mm 2 .
6. The pole piece according to claim 1, characterized in that: The compaction density of the positive electrode active material layer on the current collector is 2.2-2.5 times the compaction density of the negative electrode active material layer; Optionally, the compaction density of the positive electrode active material layer is 3.21 to 3.6 g / cm 3 The compaction density of the negative electrode active material layer is 1.39 to 1.45 g / cm 3 .
7. The pole piece according to claim 5 or 6, characterized in that: The positive electrode active material layer comprises a positive electrode active material, a first conductive agent and a first binder, wherein the mass ratio of the positive electrode active material, the first conductive agent and the first binder is: (93-95): (4-6): (0.9-1.1); and / or, The negative electrode active material layer includes a negative electrode active material, a second conductive agent, a second binder and a thickener, and the mass ratio of the negative electrode active material, the second conductive agent, the second binder and the thickener is: (95-96.5): (0.5-2): (1.8-2.2): (0.8-1.2).
8. The pole piece according to claim 7, characterized in that: The positive electrode active material includes a ternary material, the first conductive agent includes at least one of conductive carbon black, acetylene black or carbon nanotubes, and the first binder includes at least one of polyvinylidene fluoride, polytetrafluoroethylene or polyacrylic acid; and / or, The negative electrode active material includes at least one of graphite, silicon-doped graphite or silicon carbon, the second conductive agent includes at least one of conductive carbon black, acetylene black or carbon nanotubes, the second binder includes at least one of styrene-butadiene rubber, sodium alginate or polyvinyl alcohol, and the thickener includes carboxymethyl cellulose or its derivatives.
9. The pole piece according to claim 5, characterized in that: The current collector includes one, or the current collector includes at least two, and at least two of the current collectors are conductively connected.
10. A battery, characterized in that: A pole piece prepared by the preparation method according to any one of claims 1 to 4 or a pole piece according to any one of claims 5 to 9; The solid electrolyte layer is arranged between the positive electrode and the negative electrode of two adjacent pole pieces.
Citation Information
Patent Citations
Bipolar pole piece and preparation method thereof, lithium ion battery and preparation method thereof
CN111430671A
High-voltage sodium ion battery winding structure and use method thereof
CN114597507A
Negative plate and battery using same
CN115377353A
Bipolar pole piece and sodium ion bipolar battery
CN115483360A
Pole piece coating structure and method
CN115632102A